Effervescent N-Acetylcysteine Tablets versus Oral Solution N-Acetylcysteine in Fasting Healthy Adults: An Open-Label, Randomized, Single-Dose, Crossover, Relative Bioavailability Study - Spencer C. Greene, MD, FACEP, FACMT; Patrick K. Noonan, PhD; Carlos Sanabria, MD, FACP; W. Frank Peacock, MD, FACEP, FACC (Elsevier, 2016)
Background: Oral solution N-acetylcysteine (NAC) is an antidote for acetaminophen overdose, but its unpleasant taste and aroma can impede delivery even after the coadministration of antiemetic medications. Flavored effervescent NAC tablets dissolved in water might be a more palatable formulation than oral solution NAC diluted with soft drink. Objectives: To evaluate the relative bioavailability of these 2 formulations and assess subjective preferences between them. Methods: Thirty healthy adult volunteers (mean [SD] = 35.2 [9.14] years) were enrolled in this open-label, randomized, single-dose, crossover study, with a 7-day washout period. Volunteers were randomized to receive 11 g effervescent test formulation or the reference product under fasting conditions, after which 19 serial blood samples were collected over 48 hours. Total plasma NAC concentrations were evaluated by LC-MS, and pharmacokinetic parameters were calculated. The 2 formulations were considered bioequivalent if the 90% CIs of log-transformed ratios of pharmacokinetic parameters were within the predetermined bioequivalence range (80%-125%) established by the US Food and Drug Administration. Within 15 minutes of dosing, subjects were also asked to rank formulation attributes on a 5-point hedonic scale, with mean group differences analyzed by Wilcoxon signed rank test. Safety-profile assessment included treatment-emergent adverse events, physical examination, chemistry, and hematology parameters. Results: The concentration-versus-time profiles were similar for the 2 formulations, with mean Cmax of 26.5 μg/mL for effervescent NAC tablets and 28.4 μg/mL for oral solution NAC. The 90% CIs for the pharmacokinetic parameters met the criteria for concluding bioequivalence, and subjects preferred effervescent NAC tablets in terms of taste (P = 0.0247), flavor (P = 0.0082), texture (P = 0.009), and overall likeability (P = 0.0012), but there was no difference for smell (P = 0.0533). All treatment-emergent adverse events were mild, with no differences between the treatment groups. Conclusions: Data from this study of a single dose of 11 g oral NAC demonstrated that effervescent NAC tablets and oral solution NAC met the regulatory criteria for bioequivalence in fasting healthy adult subjects. Effervescent NAC tablets appear to be a more palatable alternative for treatment of acetaminophen overdose. ClinicalTrials.gov identifier: NCT02723669.